Persulfidation protects from oxidative stress under nonphotorespiratory conditions in Arabidopsis. Issue 4 (18th March 2023) - García‐Calderón, Margarita; Vignane, Thibaut; Filipovic, Milos R.; Ruiz, M. Teresa; Romero, Luis C.; Márquez, Antonio J.; Gotor, Cecilia; Aroca, Angeles
Summary: Hydrogen sulfide is a signaling molecule in plants that regulates essential biological processes through protein persulfidation. However, little is known about sulfide‐mediated regulation in relation to photorespiration. Here, we performed label‐free quantitative proteomic analysis and observed a high impact on protein persulfidation levels when plants grown under nonphotorespiratory conditions were transferred to air, with 98.7% of the identified proteins being more persulfidated under suppressed photorespiration. Interestingly, a higher level of reactive oxygen species (ROS) was detected under nonphotorespiratory conditions. Analysis of the effect of sulfide on aspects associated with non‐ or photorespiratory growth conditions has demonstrated that it protects plants grown under suppressed photorespiration. Thus, sulfide amends the imbalance of carbon/nitrogen and restores ATP levels to concentrations like those of air‐grown plants; balances the high level of ROS in plants under nonphotorespiratory conditions to reach a cellular redox state similar to that in air‐grown plants; and regulates stomatal closure, to decrease the high guard cell ROS levels and induce stomatal aperture. In this way, sulfide signals the CO2 ‐dependent stomata movement, in the opposite direction of the established abscisic acid‐dependent movement. Our findings suggest that the high persulfidation level under suppressed photorespiration reveals an essential role of sulfide signaling under these conditions.